2006
DOI: 10.1589/jpts.18.11
|View full text |Cite
|
Sign up to set email alerts
|

Knee Joint Angle at the Time of Adjustment to Submaximal Jumping in Healthy Men

Abstract: We examined the correlation between jump distance and the maximum flexion angle of the knee joint during jumping to evaluate whether healthy men adjust to jump distance by changing the angle of the knee joint. Fourteen subjects jumped 3 times with their eyes closed to each of what they thought was 25%, 50%, and 75% of their maximum jump distance, a total of 9 jumps for both the vertical and standing broad jump. We measured the knee joint flexion angle at the time of the motion and examined the correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A jump performed to a submaximal height has a slightly different movement pattern compared with the maximum jump. A jump to the maximum height is characterized by a greater range of movement in the joints of the lower limbs to achieve greater kinetic energy in the countermovement phase ( 4 , 19 ). Changes are also observed in the proportions of individual muscle and joint contributions ( 8 , 22 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A jump performed to a submaximal height has a slightly different movement pattern compared with the maximum jump. A jump to the maximum height is characterized by a greater range of movement in the joints of the lower limbs to achieve greater kinetic energy in the countermovement phase ( 4 , 19 ). Changes are also observed in the proportions of individual muscle and joint contributions ( 8 , 22 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kai et al ( 19 ) reported a relationship between the vertical jump height and knee joint flexion angle. Furthermore, Vanrenterghem et al ( 41 ) concluded that movement effectiveness (energy cost reduction) is a driving criterion of the submaximal jump performance technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg muscle power is determinant for higher jumping; however, many other factors, such as the variety of training modalities (e.g., weight training) [11], plyometric [12], electro-stimulation training [13], jumping techniques, and joint mobility could improve block skills through jumping performance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%